Genetic factors related to gastric cancer susceptibility identified using a genome‐wide association study - Saeki, Norihisa (Cancer Sci, 2012)
Gastric cancer (GC) is one of the major malignant diseases worldwide, especially in Asia, where Japan and Korea have the highest incidence in the world. Gastric cancer is classified into intestinal and diffuse types. While the former is almost absolutely caused by Helicobacter pylori infection as the initial insult, the latter seems to include cases in which the role of infection is limited, if any, and a contribution of genetic factors is anticipated. Previously, we performed a genome‐wide association study (GWAS) on diffuse‐type GC by using single nucleotide polymorphisms (SNP) catalogued for Japanese population (JSNP), and identified a prostate stem cell antigen (PSCA) gene encoding a glycosylphosphatidylinositol‐anchored cell surface antigen as a GC susceptibility gene. From the second candidate locus identified using the GWAS, 1q22, we found the Mucin 1 (MUC1) gene encoding a cell membrane‐bound mucin protein as another gene related to diffuse‐type GC. A two‐allele analysis based on risk genotypes of the two genes revealed approximately 95% of Japanese population have at least one of the two risk genotypes, and approximately 56% of the population have both risk genotypes. The two‐SNP genotype might offer ample room to further stratify a high GC risk subpopulation in Japan and Asia by adding another genetic and/or non‐genetic factor. Recently, a GWAS on the Chinese population disclosed an additional three GC susceptibility loci: 3q13.31, 5p13.1 and 10q23. (Cancer Sci 2013; 104: 1–8)